2021
DOI: 10.1177/20494637211045898
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare resource utilisation and cost analysis associated with opioid analgesic use for non-cancer pain: A case-control, retrospective study between 2005 and 2015

Abstract: Objective To examine differences in healthcare utilisation and costs associated with opioid prescriptions for non-cancer pain issued in primary care. Method A longitudinal, case-control study retrospectively examined Welsh healthcare data for the period 1 January 2005–31 December 2015. Data were extracted from the Secure Anonymised Information Linkage (SAIL) databank. Subjects, aged 18 years and over, were included if their primary care record contained at least one of six overarching pain diagnoses during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Patients with a daily use of opioids tend to seek medical help more frequently than patients without such usage. [12][13][14] Several studies have suggested that patients with daily use of opioids and patients in substitution programmes have a higher risk of insufficient pain treatment during hospitalisation than other patients. [15][16][17] Very few studies have investigated whether this also applies to patients who have a daily or regular use of opioids when presenting in the ED with acute pain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with a daily use of opioids tend to seek medical help more frequently than patients without such usage. [12][13][14] Several studies have suggested that patients with daily use of opioids and patients in substitution programmes have a higher risk of insufficient pain treatment during hospitalisation than other patients. [15][16][17] Very few studies have investigated whether this also applies to patients who have a daily or regular use of opioids when presenting in the ED with acute pain.…”
Section: Introductionmentioning
confidence: 99%
“…Adding to this are individuals who misuse opioids and patients in substitution programmes with, for example, methadone. Patients with a daily use of opioids tend to seek medical help more frequently than patients without such usage 12–14 …”
Section: Introductionmentioning
confidence: 99%